Proceedings of the 18th International Seminar on Paste and Thickened Tailings 2015
DOI: 10.36487/acg_rep/1504_09_riley
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-modified tailings deposition – ongoing testing and potential storage efficiency opportunities

Abstract: An emerging technology, known by various names such as in-line flocculation, polymer modified tailings deposition or more commercially as enhanced tailings disposal (ETD), is the subject of growing interest from mining operations. Business drivers for the mine tailings facility owners can include a variety of site-specific, material-dependant operational challenges, as well as more general desires to improve efficiency at tailings storage facilities (TSFs). Polymers can modify the behaviour of tailings in a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Owing to the increased application of forms of PT, studies to characterise the effects PT may have on post-deposition geotechnical behaviour of the treated slurry have been undertaken. Broadly, these studies have indicated the following effects of PT: lower consolidated densities at a given vertical effective stress and higher permeability at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Manzotti et al 2014;Beveridge et al 2015;Gholami & Simms 2015;Reid & Boshoff 2015;Riley et al 2015;Znidarcic et al 2015;Reid & Fourie 2016, 2018aAbdulnabi et al 2022), higher undrained shear strengths at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Beier et al 2013;Manzotti et al 2014;Cooling & Beveridge 2015;Gholami & Simms 2015;Reid & Fourie 2016Abdulnabi et al 2022) and higher CSL elevation (Reid & Fourie 2016), and various contrasting outcomes when examining the effects of PT on brittleness in undrained monotonic or post-cyclic shearing (Beier et al 2013;Gholami & Simms 2015;Reid & Fourie 2017) and drastically different penetrometer responses (Reid and Fourie 2018a), with a summary of recent studies provided by Reid and Fourie (2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the increased application of forms of PT, studies to characterise the effects PT may have on post-deposition geotechnical behaviour of the treated slurry have been undertaken. Broadly, these studies have indicated the following effects of PT: lower consolidated densities at a given vertical effective stress and higher permeability at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Manzotti et al 2014;Beveridge et al 2015;Gholami & Simms 2015;Reid & Boshoff 2015;Riley et al 2015;Znidarcic et al 2015;Reid & Fourie 2016, 2018aAbdulnabi et al 2022), higher undrained shear strengths at a given density (Jeeravipoolvarn et al 2009;Yao 2012;Beier et al 2013;Manzotti et al 2014;Cooling & Beveridge 2015;Gholami & Simms 2015;Reid & Fourie 2016Abdulnabi et al 2022) and higher CSL elevation (Reid & Fourie 2016), and various contrasting outcomes when examining the effects of PT on brittleness in undrained monotonic or post-cyclic shearing (Beier et al 2013;Gholami & Simms 2015;Reid & Fourie 2017) and drastically different penetrometer responses (Reid and Fourie 2018a), with a summary of recent studies provided by Reid and Fourie (2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The method of applying polymers to treat tailings is known as in-line flocculation or in-line polymer addition (Wells and Riley, 2007., Bembrick, 2008., Wells et al 2011., Mizani, 2013., Guang et. al, 2014., Riley and Utting, 2014., Guang and Longo, 2017., Costine et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to improve the dewatering behaviour of tailings through the addition of polymers at the point of discharge appear to have been first attempted in the early 1980s on coal tailings (Backer & Busch 1981;Stewart et al 1986). Significant interest has developed more recently, with a variety of applications on a number of tailings types over the past 10 years (Cooling & Beveridge 2015;Jeeravipoolvarn et al 2009;Riley et al 2015). An area of particular focus has been mature fine tailings (MFT), which is the very fine tailings resulting from processing oil sands, owing to the closure challenges related to that material type.…”
Section: Introductionmentioning
confidence: 99%